2022
DOI: 10.1186/s12711-022-00764-0
|View full text |Cite
|
Sign up to set email alerts
|

Can breeders prevent pathogen adaptation when selecting for increased resistance to infectious diseases?

Abstract: Background Recent research shows that genetic selection has high potential to reduce the prevalence of infectious diseases in livestock. However, like all interventions that target infectious diseases, genetic selection of livestock can exert selection pressure on pathogen populations. Such selection on the pathogen may lead to escape strategies and reduce the effect of selection of livestock for disease resistance. Thus, to successfully breed livestock for lower disease prevalence, it is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Furthermore, our recent research (Nguyen et al, in preparation) has demonstrated that conventional quantitative genetic models are inadequate for maximizing genetic gains within selected populations. Therefore, breeding objectives of genetic improvement programs for aquaculture species should be expanded to enhance epidemiological host traits, encompassing susceptibility, infectivity, and recovery [79,80]. This approach aims to fortify the overall resilience of the entire populations rather than individual animals [81][82][83].…”
Section: Enhancing Overall Immune Response and Epidemiological Host T...mentioning
confidence: 99%
“…Furthermore, our recent research (Nguyen et al, in preparation) has demonstrated that conventional quantitative genetic models are inadequate for maximizing genetic gains within selected populations. Therefore, breeding objectives of genetic improvement programs for aquaculture species should be expanded to enhance epidemiological host traits, encompassing susceptibility, infectivity, and recovery [79,80]. This approach aims to fortify the overall resilience of the entire populations rather than individual animals [81][82][83].…”
Section: Enhancing Overall Immune Response and Epidemiological Host T...mentioning
confidence: 99%
“…Furthermore, our recent research (Nguyen et al, in preparation) has demonstrated that conventional quantitative genetic models are inadequate for maximizing genetic gains within selected populations. Therefore, breeding objectives of genetic improvement programs for aquaculture species should be expanded to enhance epidemiological host traits, encompassing susceptibility, infectivity, and recovery [78,79]. This approach aims to fortify the overall resilience of the entire populations rather than individual animals [80][81][82].…”
Section: Enhancing Overall Immune Response and Epidemiological Host T...mentioning
confidence: 99%